LKPD Analysis of HOTS Type in Mathematics Learning for Elementary School Grade IV - Hawa, Siti; Toybah, Toybah; Suratmi, Suratmi; Khairunnisa, Khairunnisa (International Conference on Elementary Education, 2020)
This research aims to describe the HOTS type analysis of teacher's LKPD two dimensional figure of mathematics for elementary school' student grade VI. The research is using description of qualitative method. Subject of the research is the guide teacher who teaches in class VI of elementary school in Palembang City. Data were collected using questionnaire. The result showed that the quality of the HOTS type analysis, especially in Palembang is quite better. Although, the implementation of HOTS type analysis of teacher's LKPD is still reducing. It's caused a difficulty at cognitive HOTS level. So, based on the results of the study need to develop a compiling guide with HOTS type analysis for math lesson in elementary school's grade